Characterization of stripe rust resistance and yield-related traits in an ‘Overley’ x ‘Overland’ population - Mustahsan, Wardah K. (Kansas State University, 2022)
Wheat is a vital cereal crop, providing 20 % of the daily nutritional requirements for consumers worldwide. Although there has been a substantial increase in production and yield gains, food demands will still be on the rise in future decades, and wheat yields must continue to increase rapidly to meet these demands. Grain yield can be inhibited by biotic factors (pathogens), which require the development of resistant varieties against pathogens. Stripe (yellow) rust produces massive yield losses in wheat production, and ample resistance against stripe rust is achieved by pyramiding multiple resistant genes together. Yield also can be improved by characterizing the underlying mechanisms that define yield and yield-related traits. We used breeding technology tools to dissect the genetic architecture of yield-related traits, yield, and stripe rust resistance to identify genomic regions that can improve these traits in wheat germplasm and broaden the genetic resources available for breeders to develop robust breeding germplasm that can improve the profitability and resilience of wheat production. Stripe (yellow) rust, caused by Puccinia striiformis (Pst), is a devastating disease of wheat worldwide. In commercial production, stripe rust reduces forage yield, grain yield and grain quality. Yield losses caused by stripe rust range from 10% to 70%. This study was conducted using two different wheat reference genomes (IWGSC v2.1(‘Chinese Spring’) and ‘Jagger’) to identify quantitative trait loci (QTL) associated with adult plant field resistance to stripe rust in the hard winter wheat RIL population, ‘Overley’ x ‘Overland’ to provide breeders with identified genomic regions associated with quantitative field resistance. Our QTL analysis identified genomic regions on 2AS (2N[superscript v]S translocation), 2BS, 2BL, and 2DL using two different mapping methods (Inclusive Composite Interval Mapping and Multi-Environmental Trial Analysis) that were associated with stripe rust resistance for both infection type and severity using genetic maps from both genomes. There were no meaningful differences in interpreting the data from the two maps. Overley contributed the resistance alleles at the 2AS and 2BL QTLs. Overland contributed the resistance alleles at the 2BS and 2DL QTLs. The 2DL QTL (QYr.hwwg-2D) will be further refined due its environmental stability for resistance. We designed PCR-based SNP marker assays to efficiently identify these genomic regions in breeding populations. Yield improvement can be facilitated by a deeper understanding of the underlying infrastructure of components that determine grain yield. We performed a QTL analysis on the population Overley x Overland, to identify genomic regions in our population can explain the variation in yield and its components in field trials using the two different reference maps. We identified major QTLs in both reference maps for yield (3BL), single kernel weight (4AL), plant height (6AS), grains per spike (4AL), thousand grain weight (4AL), and physiological maturity (2BS). The Jagger map identified more QTLs (40 QTLs) than the IWGSCv2.1 map (30 QTLs). The future direction of these studies will be marker development to utilize these QTLs in yield-improvement breeding programs.
Keywords: Stripe rust; Hard winter wheat; Yield; Quantitative trait locus